Cytokinins on the Move - Durán-Medina, Yolanda; Díaz-Ramírez, David; Marsch-Martínez, Nayelli (Frontiers in Plant Science, 2017)
Cytokinins are important signals that participate in different plant processes, and are well known for their strong influence in plant development. With the years, knowledge has been built about their effects, chemical nature, metabolism, and signaling mechanisms. However, one aspect about cytokinins that has been lagging behind is cytokinin transport. Recent reports are providing more information about how cytokinins are transported and how their transport is connected to their effects in development. This minireview provides a general overview of what is currently known about cytokinin transport, with a focus on the latest reports.